Formalismo Pós-Newtoniano parametrizado e extensões de relatividade geral. - Bertini, Nicolas Ribeiro (2017)
Here we present the Post-Newtonian Parametrized (PPN) formalism, as developed by Will and Nordtvedt, and we apply it to general relativity, Brans-Dicke and RGGR (Renormalization Group extended General Relativity) theories. This formalism can be applied to several metric theories of gravity. It relates the coefficients of a post-Newtonian expansion to the observed gravitational effects at the Solar System. Besides a review on the PPN formalism, here we detail part of its observational roots. Its application to RGGR was in part recently done, by using the Eddington parametrization, which considers the gravitational source to be a static point particle and depends on two parameters. We present the full PPN formalism application, which depends on ten parameters and consider matter fluids instead of point particles. Through this analysis we confirm the validity of the previous results from a more clear and robust procedure. Moreover, we extend the observational constraints towards less restrictive realizations of RGGR (namely, without specifying a particular ß-function to the gravitational coupling parameter G).